Marianismo and the changing role of Latinas in educational leadership - Salazar Montoya, LeAnne C.; Kew, Kristin (Frontiers in Education, 2023)
This paper amplifies the testimonios of accomplished Latina school leaders regarding their upbringing, familial responsibilities, generational poverty, and commitment to change the narrative and break through institutional barriers. Cultural norms, familial responsibilities, and uncommon mentorship models of these women are discussed. The women in our research serve as femtors to other women in the field by breaking glass ceilings built for and sustained by hegemonic systemic structures that perpetuate existing stratus. Our findings of these testimonios fully capture the authenticity and essence of the participants' lived experiences, while utilizing a feminist framework to construct research. The themes that emerged include (1) foster a professional community linking you to other educational professionals, (2) participate in structured mentorship development programs throughout your career, (3) remain a lifelong learner, (4) professional relationships matter, and (5) remain confident, yet humble, and be your authentic self. The pathways of the women in this study were similar in that their decisions led to positions of authority, namely the superintendency, and recognition for breaking through the traditional glass ceiling. We must consider whether generations of Latinas did not pursue careers or leadership positions outside their homes due to what they feel are their cultural and family obligations. Gil and Vazquez (1996) presented the concept of marianismo in their work: "In today's North America, marianismo is the invisible yoke which binds capable, intelligent, ambitious Latinas . . . to a no-win lifestyle" (p. 7).